Synthesis of Novel Peptide Dendrimers PDL-GB2 and PDL-G2 - Lin Yunzhu; Weng Lingling; Qi Qingrong (The Scientific World Journal)
Peptide dendrimers are a novel type of macromolecules with precise structure, which can be used as drug target vector and controlled-release carrier. So it is valuable to study. In this paper, novel peptide dendrimers PDL-GB2 and PDL-G2 were prepared according to divergent procedure with four-orientation molecule as the core and L-lysine as the branch unit. And the structures were identified by 1HNMR, 13CNMR, MS, and elemental analysis.